Anchoring Effects and Valuation Persistence in the Indonesian Consumer Non-Cyclical Sector: A Dynamic System GMM Approach - Abdul Mukti Soma; Shohifuddin, Mas Mochamad (PT FORMOSA CENDEKIA GLOBAL, 2026)
This study investigates market valuation determinants within the Indonesian consumer non-cyclical sector (2018–2024). Utilizing a dynamic System Generalized Method of Moments (System GMM) approach on 58 firms, the research examines the impact of Altman Z”-Score, Piotroski F-Score, Mohanram G-Score, and Beneish M-Score on Price to Book Value. Findings reveal strong valuation persistence, where lagged Price-to-book Value (PBV) serves as the primary anchor, while traditional accounting signals exhibit limited immediate influence. This highlights the psychological-adaptive nature of defensive sector valuations in emerging markets. The results suggest that historical momentum outweighs conventional fundamental signals, contributing to the literature on valuation inertia and signaling effectiveness in stable industries. This research provides critical insights for investors navigating defensive asset pricing.